ENTEROTOXIN PRODUCTION IN STRAINS OF CAMPYLOBACTER-JEJUNI, ISOLATED FROM SWINE DIARRHEA - Decarvalho, ACDB; Mos, E. N.; Shockeniturrino, R. P. (Soc Brasileira Microbiologia, 1993)
One hundred and twenty-six strains of Campylobacter jejuni isolated from swine with diarrhea were examined for the production of enteroxin, by culture filtrate inoculation into ileal loops in several animal species.Four (3,1 %) of the strains tested produced fluid in ligated ileal loop of albino rabbit, 19 (15 %) in rat and 14(11, 1 %) in swine. By the test of intragastric inoculation in suckling mouse, none of the strains revealed capacity to produce enterotoxin, although two strains were considered suspicious. Twelve (54,5 %) of the strains that induced ileal fluid in rat and swine produced cytotoxic effect in monkey kidney cells (Vero), affecting up to 60 % of the monolayer. However, no alteration was observed in hamster kidney cells (BHK).
Keywords: CAMPYLOBACTER-JEJUNI; ENTEROTOXIN; SWINE DIARRHEA; PATHOGENICITY